Co-morbidities, Maternal and Fetal Outcome of Teenage Pregnancy at Tertiary Care Hospital, Nepal (Kathmandu University Medical Journal, 2020)
Background Teenage pregnancies constitute a serious health and social problem worldwide. World estimates in 2008 report about 16 million births to adolescent mothers, most of them occurring in low and middle income countries. Objective To assess pregnancy co-morbidities and outcome of teenage pregnancy. Method A cross-sectional study was conducted at obstetrics and gynecological department of Dhulikhel Hospital. Study was conducted for 18 month period from 1-07-2013 to 30-12-2014. All teenage pregnancy cases admitted at the time of study period were enrolled. Purposive sampling technique was used. Data were collected by face to face interview using clinical Performa and through record file of the patient. Collected data were analyzed in SPSS version 21.0. Result Total of 527 teenage mothers of varying age group (15 to 19 years) were enrolled in the study. Teenagers who had never been to school were 3.0%; 66.2% of them were from low socioeconomic background , and 58.6% were from rural areas. Pregnancy co-morbidities detected were, Urinary tract infection (UTI) 18.4%, threatened preterm 12.9% followed by ante partum hemorrhage 4.7%. However, other major co-morbidities such as hypertensive disorder, gestational diabetes found to be very less such as, hypertension 0.8% and gestational diabetes found in only one woman. Conclusion Maternal and newborn outcome and co-morbidities among teenage pregnant women found less compare to other studies. Major pregnancy related morbidities such as hypertension, pre-eclampsia and diabetes were found very less. Most common maternal morbidity found was urinary tract infection during pregnancy but statistically not significant. Similarly, newborn mean weight was more than 2.5 kg and neonatal death found very less. However, teenage pregnancy is significantly associated with low economic status, illiteracy status, willingness to marriage by teenagers and ethnicity.